Innovation of Sustainable Management Models Oriented towards Circular Economy in Manufacturing Enterprises: Micro Practices Based on Industrial Chain Collaboration - Wang, KunYu; Shen, LieZhi (International Journal of Multidisciplinary Research, 2026)
Gainst the backdrop of dual carbon goals and stricter global green trade rules, manufacturing enterprises face micro-challenges like insufficient industrial chain synergy and cost-benefit imbalance in sustainable management transformation. Focusing on their circular economy pain points, this paper explores three innovative paths: circular production system, digital control platform, and stakeholder co-governance, verified by three typical enterprise cases and visual data. The study shows that connecting industrial chain synergy links enables enterprises to balance economic and environmental benefits. It provides implementable guidance for similar enterprises and micro-perspective reference for sub-sector research, with future extension to electronic and chemical manufacturing.